The search and the eye tracking: a semiotic overlook about the knowledge graph - Monteiro, Silvana Drumond; Rodas, Cecilio Merlotti; Vidotti, Silvana Aparecida Borsetti Gregorio (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2020)
The eye tracking is, at the same time, a technology and a research method used in several areas of knowledge and, recently, in the area of Information Science. Its main thesis, formulated by Just and Carpenter (1976), is the strong eye-mind hypothesis, that is a strong relation between visualization and information processing. In this direction, a basic research was done with an experimental design, aiming to evaluate the search behavior in a Search Engine Results Page (SERP) of Google, especially the visualization of the Knowledge Graph (KG) or Knowledge Map. The research proposition was based on the Peirce's Semiotics, in which signs in a search result (SERP), to a lesser or greater extent, can influence choices, qualify results, capture the look and be important or determinant in a choice from a search, explaining the strong eye-mind. The results demonstrated that the image is a cognitive attractor; however, the choice also depends on other factors, such as the type of search and the habit of the subject in searches in search engines.
Keywords: Eye Tracking; Peirce' s Semiotics; Knowledge Graph; Google; Taxonomy of Web Search